2019
DOI: 10.1002/iid3.249
|View full text |Cite
|
Sign up to set email alerts
|

IL‐2 modulates Th2 cell responses to glucocorticosteroid: A cause of persistent type 2 inflammation?

Abstract: Background Glucocorticosteroids (GCs) are the main treatment for asthma as they reduce type 2 cytokine expression and induce apoptosis. Asthma severity is associated with type 2 inflammation, circulating Th2 cells and higher GC requirements. Objective The aim of this study was to assess whether ex vivo production of interleukin 2 (IL‐2), a T‐cell survival factor, associated with clinical features of asthma severity, the proportion of blood Th2 cells and Th2 cell responses to GC. Methods Peripheral blood from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
5
18
0
Order By: Relevance
“…This result indicates that in vivo type 2 cytokines are likely su ciently controlled with an optimal dose of either prednisolone or dexamethasone and, in line with other reports, are anticipated to reduce the proportion of CD4 + T cells expressing IL-4 and IL-5 [50]. However, we recently showed that the suppressive effect of dexamethasone on IL-13 was reversed after activation unless cells were continuously exposed to dexamethasone [45], suggesting the effect could be temporary. The lack of increase in IL-10 or IL-17 following dexamethasone treatment [45], coupled with our new data showing that dexamethasone reduced IFNg mRNA levels (Table 1), indicates active suppression of type 2 cytokine transcription, rather than shifting Th2 cells toward a Th1, Th17 or T regulatory cell phenotype.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This result indicates that in vivo type 2 cytokines are likely su ciently controlled with an optimal dose of either prednisolone or dexamethasone and, in line with other reports, are anticipated to reduce the proportion of CD4 + T cells expressing IL-4 and IL-5 [50]. However, we recently showed that the suppressive effect of dexamethasone on IL-13 was reversed after activation unless cells were continuously exposed to dexamethasone [45], suggesting the effect could be temporary. The lack of increase in IL-10 or IL-17 following dexamethasone treatment [45], coupled with our new data showing that dexamethasone reduced IFNg mRNA levels (Table 1), indicates active suppression of type 2 cytokine transcription, rather than shifting Th2 cells toward a Th1, Th17 or T regulatory cell phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…Early apoptotic cells were identi ed as those staining for Annexin V only, but not 7-AAD, and cells positive for 7-AAD alone were considered necrotic ( Figure S3). We recently reported similar responses to dexamethasone-induced apoptosis when comparing the CCRF-CEM cell line to primary Th2 cells [45]. When we examined the response to prednisolone and dexamethasone we found that both CSs induce necrosis of CCRF-CEM cells in a dose dependent manner (Figure 2A).…”
Section: Dexamethasone More Potently Reduces Type 2 Cytokine Levels Tsupporting
confidence: 67%
See 3 more Smart Citations